An Analysis of Metaphorical Expressions in Teenager’s Fiction Novels - Gata Khumaira; Iskandar Abdul Samad; Tengku Maya Silviyanti (Universitas Syiah Kuala, 2020)
Figurative language has important role in literature. Figurative language makes the literature works more interesting to read and it has certain deep meaning. Two fiction novels entitled “The Three Musketeers” written by Alexandre Dumas and “Assassin’s Creed Unity” written by Oliver Bowden were chosen as research data. The aims of this research are to analyze Metaphor found in the four chapters of the novels and the implied meaning of Metaphor found in it. In analyzing the data, the researcher used content analysis proposed by Kuhatna (2006) stated that content data analysis is a symbolic meaning. The research shows that there were 71 metaphor expressions found in two teenager’s fiction novels, such as: Active Metaphor (17 expressions), Ontological Metaphor (21 expressions), Complex Metaphor (17 expressions), Conceptual Metaphor (11 expressions) and Dead Metaphor (5 expressions). Those 71 Metaphor types are then categorized as types of Metaphor proposed by Lakoff and Johnson (2003) and Richards (2009). The results of these Metaphor expressions enhanced the deep meaning in the sentences in the novels mentioned above and make it more artistic.